(3GdLhGgQ GdhajI aj GdObGFb GdLaQjIs
(3ChdgG (B:s
(3gPG eNJUQ aj GdahGFO GdLaQjI ef bhd GdEeGe Ydj Hf ehSi GdQVj Ydjg GdJMjI hGdSdGe, MjK bGd Ef gPG GdYde efShH s
(3BNQgG (B:s
(3hEf cGf GdeWdhH dg fSHI HSGFQ GdchGcH aJYed gPg GdcjajI jchf Yedc eYJHQkG aj GdZGjI hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQcRjI GdYGeI (B- (3GdehUd (B(300 (3L(B) s
Keywords: (3GdMQha h GdChaGbs